COMPARATIVE ANALYSIS OF THE USAGE OF WHATSAPP AS A LEARNING APPLICATION DURING THE COVID-19 PANDEMIC IN ELEMENTARY SCHOOL AND JUNIOR HIGH SCHOOL STUDENTS - Rinda Nuningtyas; Bambang Widi Pratolo; Arina Athiyallah (Premise: Journal of English Education and Applied Linguistics, 2021)
During the Covid-19 pandemic, there was a very significant change in student teaching and learning methods.The government policy requires that almost all activities including learning activities at school be eliminated and replaced with online schools. One of the most used applications for learning in this pandemic era is WhatsApp. The general objective of this research is to conduct a comparative study on the use of the WhatsApp application as a learning application during the Covid-19 pandemic in elementary and junior high school students in English. While the specific purpose of this research is to find out the strengths and weaknesses as well as the constraints of using WhatsApp as a learning application. The research method used is through field observations using qualitative descriptive methods and also interview techniques to several elementary and junior high school students in the research environment. This is interesting to research further based on direct observations of researchers on the use of WhatsApp on school students directly. This study assumes that the advantages and disadvantages of the learning process using WhatsApp will be found for both elementary school students and junior high school students. That elementary school finds difficulty in using WhatsApp for learning. Because some of the elementary students are still not fluent in reading. Junior high school learners assume that learning by WhatsApp is efficient but still not comparable to face-to-face meetings. The research implications are as follows:  that the students would be able to learn easily by using WhatsApp as a learning application. The teacher Would find another method that enhances the understanding of the students besides using WhatsApp by necessity.